Survival and fecundity of Dichroplus maculipennis and Ronderosia bergi (Orthoptera: Acrididae: Melanoplinae) following infection by Beauveria bassiana (Ascomycota: Hypocreales) under laboratory conditions - Pelizza, Sebastián Alberto (2013)
This study examined the effects of strain Beauveria bassiana (LPSC 1067) on nymphal development time, fecundity and adult survival in Dichroplus maculipennis and Ronderosia bergi under laboratory conditions. It was observed that infection with 1 103 conidia/ml altered nymphal development time, fecundity and adult survival in both species. Mortality of D. maculipennis during third through the last instar (sixth) was significantly higher among treated nymphs (6693.8%) than in controls (1591.7%). Similarly, mortality in R. bergi during third through the last instar (fifth) was higher in treated nymphs (7192.8%) than in controls (1991.5%). Nymphal development times of both infected D. maculipennis and R. bergi were longer than controls. On the other hand, among survivors of both the species, control adults lived longer than infected adults. Finally, control grasshoppers of both species were much more successful reproductively than infected grasshoppers.